The Complexity of Parenthood in Forced Migration : Risks, Commitments and Dilemmas - Sunagic, Lejla (Population, Space and Place, 2025)
Clandestine migration is not only a response to precarious living conditions but also driven by aspirations and desires for change that migrants carry into their journeys. Yet, far less is known about what becomes of these subjective driving forces once people reach their destinations and settle down. To address this gap, this study explores how Syrian parents who risked crossing the Mediterranean to reach Europe interpret their migration from the standpoint of their settled lives. This perspective allows for tracing how the reasoning behind the risky decision evolved—from its origins in Syria (or the first country of asylum) to reflections rooted in the host countries of Sweden and Denmark. Across these spatial and temporal shifts, parents' narratives reveal the contradictory values they attach to migration, shaped by the complex dynamics of parent–child relationships. These contradictions are examined through the lens of the moral theory of risk. From this perspective, the notion of virtuous risking for the sake of one's children—initially central to parents' justification of their decision—gradually loses significance within the context of their new lives in Europe. This dynamic lies at the core of the evolving meanings parents attach to both risk and migration.
Publisher Copyright: © 2025 The Author(s). Population, Space and Place published by John Wiley & Sons Ltd.
Keywords: clandestine journey; migration; parenthood; refugees; risk